Հայ մտավորականությունը` ցեղասպանության զոհ - Աթայան, Անահիտ (ԱրՊՀ հրատ․)
Статья «Армянская интеллигенция - жертва геноцида» рассматривает судьбу армянской интеллигенции, ставшей жертвой геноцида 1915г. Были схвачены и высланы сливки армянской интеллигенции – самым жестоким образом уничтожены в пустынях. Известна политика турок: если хочешь сломить нацию – обезглавь ее верхушку». Жертвами этой политики стали выдающиеся писатели, искусствоведы, юристы, педагоги, духовные деятели, доктора – более 800 человек различных специальностей. В историю XX в. была вписана кровавая страница - геноцид, которым было остановлено духовное продвижение древнего народа. The article «The Armenian inteligensia as a victim of the Genocide» discusses the fate of Armenian intellectuals who became victims of the Genocide in 1915. The Armenian intellectuals were arrested and executed in the most barbaric way annihilating them in deserts. It is a well – known Turkish policy «If you want to oppress a nation, behead the leaders». Famous writers, artists, lawyers, pedagogies, spiritual leaders, doctors and people of 800 different professions became the victims of this policy. In the history of mankind there was written a bloody page - Genocide, with which the spiritual flight of ancient people was stopped.
Keywords: Հայոց ցեղասպանություն; Արցախ